Urochloa decumbens pasture recovery with management systems and phosphate fertilization (Research, Society and Development, 2020)
Adequate pasture management is important to ensure animal production. The objective of this study was to evaluate the effect on shoot dry weight yield (SDWY) and mineral composition in degraded pasture (Urochloa decumbens) recovery in a Typic Oxisol with introduction of Stylosanthes and phosphorus (P) fertilization. The experiment was set up as completely randomized block design in a split-plot arrangement with four replicates. The plots were seven management system: T1 - Control Urochloa decumbens without Stylosanthes; T2 - U. decumbens + Stylosanthes with no-till; T3 - U. decumbens with partial desiccation + Stylosanthes; T4 - U. decumbens with total desiccation + Stylosanthes; T5 - U. decumbens + Stylosanthes with soil scarification; T6 - U. decumbens + Stylosanthes with plowing;  T7 - U. decumbens + Stylosanthes with plowing + harrowing and the subplots was the P fertilization (presence and absence). P fertilization (60 kg ha-1 of P2O5) increased the P concentration and SDWY of U. decumbens, while the introduction of Stylosanthes in the different management systems used did not change the forage yield.